SPECIAL ECONOMIC ZONES AS DRIVERS OF REGIONAL ECONOMIC DEVELOPMENT: BEST PRACTICES AND IMPLICATIONS FOR UZBEKISTAN - Khatamova Manzura Ochildiyevna (American Journals, 2024)
Special Economic Zones (SEZs) are considered effective tools for promoting industrialization and structural transformation, provided they are implemented appropriately in the right context. This document reviews existing practices of SEZ establishment using examples from successful countries, including China and South Korea, and explains how SEZs contribute to regional economic development.
Keywords: SEZ, economic development, cluster, free trade zone, SEZ characteristics, economic growth, multinational corporations.